A reliable multi-path cluster routing method for ground-air cooperative flying ad-hoc networks - Liu, Liming; Xu, Wenxuan; Shao, Yanling; Dong, Wenyong; Xu, Hairui; Gao, Hewen; Shan, Pingping; Guo, Junying (Computing, 2025)
Most routing methods in ground-air cooperative systems adopt the clustering technique to improve network scalability and topology management. However, their performance often degrades in highly dynamic environments due to inadequate addressing of routing problems, particularly in establishing stable and reliable flying ad-hoc networks for unmanned aerial vehicles (UAVs). In response to this challenge, this study proposes a reliable multi-path cluster routing method for flying ad-hoc networks, exemplified by a border patrol scenario. The proposed method comprises two mechanisms aimed at enhancing communication reliability: one is to use a multi-path routing strategy to select a more stable and load-balanced route to minimize the likelihood of link failure caused by node movement, and the other is to employ a greedy forwarding strategy based on geographical location to repair the broken links in cases of routing link failure. Based on the above mechanisms, network communication performance can be significantly improved, even in highly dynamic environments characterized by high mobility and drastic topology changes. We thoroughly evaluate the performance of the proposed algorithm against state-of-the-art methods using the ns-3 network simulator. The results demonstrate that the proposed method notably enhances data delivery rate and throughput while reducing task completion time.